Library Of Bank Indonesia North Sumatra Representative Office In Conducting Infopreneurship For Easy Access To User Information - Intan Humaira; Franindya Purwaningtyas (Universitas Trunodjoyo Madura, 2023)
Library as a non profit institution does not convert the infopreneurship activities into money. Instead, it distributes information and conducts informations marketing for public services. Infopreneurship at the KPw Indonesia North Sumatra Bank library is carried with the aim of disseminating information and reaching the public. Infopreneurship is done by repackaging information into new forms of information.. The repackaging information are placed at the building of the KPw library of Indonesia sumut and also distributed on the social media page in order to ease the access of information. The method used in this research is qualitative with interview and observation as the methods for data collection. This research lists three sources that are used, they are The librarian, library volunteer and library visitor including the social media’s followers of the KPw Indonesia North Sumatra Bank library. Based on the observation of the library and its social media page along with the interviews of the three sources, The result found that infopreneurship provides easier access towards the information for the library visitors without the must to visit the library directly. the presented information are concise, concrete and accurate but still remains exciting to see.